KIT DETEKSI KANKER LEHER RAHIM BERBASIS ANTIBODI TELOMERASE: PENDEKATAN SECARA IMMUNOMOLEKULAR - Hidayatullah, Furqan; Wijaya, Andreas Budi; Gersom, Camoya; Pahlevi, Faizal Reza; Setyabudhi, Veronica Verina (Program Kreativitas Mahasiswa - Penelitian, 2013)
Cervical cancer is the first leading cause of cancer death in Indonesia. About 95% telomerase activity is associated with cervical cancerâs malignancy. Therefore, telomerase is very potential as a biomarker for cervical cancer detection. This researchâs purpose is to produceÂ  cut-off point of cervical cancer telomerase. Telomerase antibody is produced and detected using Western Blotting and ELISA, 15 samples of each cancer and normal patients were collected from RSSA. ELISA Absorbance value of antibody and antigen binding were collected and analyzed using independent t-test and ROC. cut off point is found at 0.092 with 81,25% specificity and 80% sensitivity.Â Keywords: Cervical Cancer, Telomerase, Telomerase Antibody, Cut-Off point